Development and environmental sustainability through treadmill of production and metabolic rift in Cecil Rajendra’s selected poems - Fadzil, Suhada (2018)
Malaysia being one of the developing countries has always been ambitious in its journey to achieve the status of a ‘developed nation’ by year 2020. Unfortunately, the capitalist nature of its economic system has endangered the country’s most treasured heritage, which is its environment and natural resources. Therefore, there is an increasing concern about the effects of development on the environment, which have been taken for granted in the pursuit of economic progress. The emerging awareness has driven Malaysia to also work on achieving sustainable development especially when environmental sustainability is one of her goals. Changes in the environment caused by development have caught the attention of Malaysian authors and going green to preserve the environment is emerging as a popular theme in many literary works. Cecil Rajendra is among the Malaysian authors who consistently deal with environmental issues in their works. Therefore, the main aim of this study is to analyse the relationship between Malaysia’s development and its environmental sustainability in Cecil Rajendra’s selected poems produced during the period from 1978 to 2004. The objective of this study is to examine the way Cecil Rajendra illustrates Malaysia’s development and to investigate the poet’s views on Malaysia’s environmental sustainability in his selected poems. This research involves the use of two concepts under the theory of eco-Marxism which are ‘treadmill of production’ and ‘metabolic rift’. The findings of this research show that Rajendra illustrates Malaysia’s development as capitalistic and destructive to nature as it causes environmental degradation and his views of Malaysia’s development is that the country is not environmentally sustainable due to the effects of development towards the entire ecosystem.